2011
DOI: 10.1016/j.pain.2010.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coping skills training and sertraline in patients with non-cardiac chest pain: A randomized controlled study

Abstract: Non-cardiac chest pain (NCCP) is a common and distressing condition. Prior studies suggest that psychotropic medication or pain coping skills training (CST) may benefit NCCP patients. To our knowledge, no clinical trials have examined the separate and combined effects of CST and psychotropic medication in the management of NCCP. This randomized clinical trial examined the separate and combined effects of CST and antidepressant medication (sertraline) in participants with non-cardiac chest pain. A sample of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 60 publications
1
40
1
3
Order By: Relevance
“…This approach is consistent with chronic care models of care [38–42], previous collaborative care and interdisciplinary behavioral approaches to the management of chronic pain [27,35,43–46], the many studies done on the pain coping skills training approach [29,30,4749], and chronic pain treatment guideline criteria [5052]. A visual depiction of patient flow through the intervention is shown in Fig.…”
Section: Interventionsupporting
confidence: 60%
“…This approach is consistent with chronic care models of care [38–42], previous collaborative care and interdisciplinary behavioral approaches to the management of chronic pain [27,35,43–46], the many studies done on the pain coping skills training approach [29,30,4749], and chronic pain treatment guideline criteria [5052]. A visual depiction of patient flow through the intervention is shown in Fig.…”
Section: Interventionsupporting
confidence: 60%
“…In the literature identified by this systematic search, the percentage of symptom reduction ranged from 18% to 67% for the treatment of functional chest pain. [17][18][19][20][21][22][23][24] For the treatment of heartburn this percentage ranged from 23% to 61%. [26][27][28][29] Unfortunately, considerable differences between the selected studies regarding the patient definition, outcome definition, and the method of symptom analysis hampered the meta-analysis of the data presented.…”
Section: Discussionmentioning
confidence: 99%
“…A cardiac etiology and gastroesophageal reflux must be excluded, as well as other histopathology-based motility disorders such as achalasia. We identified 8 randomized, placebocontrolled trials evaluating antidepressant therapy for noncardiac chest pain, of which 6 trials were discussed extensively in a systematic review by Nguyen et al [17][18][19][20][21][22][23][24][25] The primary outcome measures in these 8 trials varied considerably, but in all trials the frequency, intensity, or duration of chest pain was evaluated. Although currently a part of the Rome III diagnostic criteria, exclusion of GERD was performed in only 2 studies, by Lee et al 22 and Clouse et al 17 Favorable results were obtained in 5 studies, whereas in the other 3 studies no beneficial effect was observed compared with placebo ( Table 2).…”
Section: Functional Chest Pain Of Presumed Esophageal Originmentioning
confidence: 99%
“…More recently, it was reported that emotion and pain are closely linked through the 5-HT system (Bushnell et al, 2013). Selective serotonin reuptake inhibitors (SSRIs), one category of antidepressants, have been reported to exert an analgesic effect by influencing emotion (Keefe et al, 2011). Like SSRIs, occupying 5-HTT in human brain with tramadol would have some kind of influence on emotion via the 5-HT system.…”
Section: Discussionmentioning
confidence: 99%